2013
DOI: 10.1186/1478-7547-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Protecting child health and nutrition status with ready-to-use food in addition to food assistance in urban Chad: a cost-effectiveness analysis

Abstract: BackgroundDespite growing interest in use of lipid nutrient supplements for preventing child malnutrition and morbidity, there is inconclusive evidence on the effectiveness, and no evidence on the cost-effectiveness of this strategy.MethodsA cost effectiveness analysis was conducted comparing costs and outcomes of two arms of a cluster randomized controlled trial implemented in eastern Chad during the 2010 hunger gap by Action contre la Faim France and Ghent University. This trial assessed the effect on child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The activities implemented closely mirror the supply, logistics, and distribution of food commodities and supplements (AB‐CCs 1 and 2) for which we calculated monthly costs of 7.79 USD for PROCOMIDA (FFR + CSB) and 7.41 USD for Tubaramure (T24). A study from Chad found that the cost per beneficiary of delivering a family ration with ready‐to‐use supplementary foods for 6‐ to 36‐month‐olds was 220.40 2010 EUR per month (Puett et al, ). The monthly cost of PROCOMIDA's programme model that provided a full family ration with LNS was considerably less expensive at 37.60 USD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities implemented closely mirror the supply, logistics, and distribution of food commodities and supplements (AB‐CCs 1 and 2) for which we calculated monthly costs of 7.79 USD for PROCOMIDA (FFR + CSB) and 7.41 USD for Tubaramure (T24). A study from Chad found that the cost per beneficiary of delivering a family ration with ready‐to‐use supplementary foods for 6‐ to 36‐month‐olds was 220.40 2010 EUR per month (Puett et al, ). The monthly cost of PROCOMIDA's programme model that provided a full family ration with LNS was considerably less expensive at 37.60 USD.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the hypothetical programme activity cost if each treatment arm was implemented at programme scale (i.e., if all programme beneficiaries received that treatment). The detailed programme description was used to identify which activities would have been conducted differently, to adjust the quantity of the inputs needed to implement these activities, and to estimate the cost of programme activities for each treatment arm–based programme models (Puett et al, ). Because the programmes had target beneficiary numbers and monitored enrolment to reach these goals, we assumed for those treatment arms with lower programme uptake that the corresponding treatment arm–based programme model would have expanded services to reach the target number of beneficiaries and adjust inputs accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Using methods common in other cost-effectiveness studies [30,31], the research team obtained incremental cost and effectiveness measures: Incremental cost per enrolled child was then linked with the specified incremental effectiveness (adjusted number of months of wasting measurements per child and adjusted prevalence of stunting at end-line), as depicted in Fig. 2.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…DALYs or QALYs), indicating a very small difference across income groups, which was not statistically significant (odds ratio = 1.24, p = 0.304). The outcome measures in natural units included 'diarrhoea case averted' (Puett et al, 2013) and 'detection of individual with high cardiovascular risk' (Selvarajah et al, 2013).…”
Section: Outcome Measuresmentioning
confidence: 99%